Post-conflict area-based regeneration policy in deprived urban neighbourhoods. Issue 6 (2nd June 2020) - Mohan, Gretta; Longo, Alberto; Kee, Frank
ABSTRACT: Neighbourhood Renewal is the main area-based urban regeneration initiative in Northern Ireland. The region is a unique setting for urban regeneration because of an enduring legacy of ethno-religious conflict. Using longitudinal micro-data, the paper investigates the effect of the policy on the economic welfare of residents living in policy-on areas compared with three policy-off control groups. Difference-in-difference regression on employment and unemployment status, household income, and benefit receipt and subjective financial status reveals that Neighbourhood Renewal did not close the gap in economic circumstances. However, the policy contended with a challenging economic period, which may have constrained the ability of areas to capitalize on the initiatives fully.